Hvad er erhvervssproglig forskning? - Kromann, Hans-Peder (HERMES - Journal of Language and Communication in Business, 1988)
During the 80’es the professional, or rather, special language research in Denmark has enjoyed political and economic support. This actualizes the need for a definition of "special language research". Danish linguistics is institutionally divided into special and ordinary linguistics. Internationally this is not typical, and it is inexpedient because of the interdependency between the two fields. Among the initial difficulties of the 15 years old special language research the most important seems to be a missing link between traditional linguistics and non-linguistic professional research. The project "Special language communication", financed by the Danish Research Council for the Humanities, should provide this missing link.